Micro search engine for IoT: an IoT search engine prototype for private networks - Habaebi, Mohamed Hadi; Al-Haddad, Ahmed; Zyoud, Alhareth; Hijazi, Ghofran (Bentham Science Publishers B.V., 2018)
Background: The Internet of Things (IoT) has been heralded as the “next big thing” waiting to be realized. IoT revolves around increased machine-to-machine communication and it encompasses various embedded sensorsand actuators that assist users in monitoring and controlling objects remotely in many fields and applications.